Phylogenetic studies of Newcastle disease virus isolated from poultry flocks in South Sulawesi Province, Indonesia, in 2019 - Saputri, Meliana Eka; Poetri, Okti Nadia; Soejoedono, Retno Damajanti (Journal of Advanced Veterinary and Animal Research, 2021)
Objective: Indonesia is one of the Newcastle disease (ND) endemic countries in the world. An outbreak of the ND virus (NDV) was first reported in Indonesia in 1926. This study aimed to detect, isolate, and classify the NDV by molecular approaches from poultry farms in South Sulawesi Province of Indonesia in 2019. Materials and Methods: As many as 36 pooling samples from the cloacal swab, trachea swab, proventriculus, and spleen tissues obtained from ND-suspected chickens were isolated in 11-day-old embryonated chicken eggs type-specific antibody-negative. The viruses were confirmed by reverse transcription-polymerase chain reaction (RT-PCR), followed by sequencing. Results: The results showed that 18 out of 36 pooling samples were NDV-positive based on the isolation result and RT-PCR test. The sequencing results showed that 10 NDV isolates had a motif 112R-R-Q-K-R-F117 in the fusion protein cleavage site region, which suggested that the NDV isolates were of virulent pathotype. The phylogenetic studies based on the F gene’s partial nucleotide sequence classified the study isolates into NDV virus genotype/subgenotype VII.2. Conclusion: These findings are expected to help provide the latest characteristic information of NDV in South Sulawesi Province to determine the seed vaccine for control strategies of ND. J. Adv. Vet. Anim. Res., 8(1): 129-137, Mar 2021 http://doi.org/10.5455/javar.2021.h495